Systematic Literature Insight into Banking Transformation - Anti Deisnasari; Diana Permata Sari (Indonesia Banking School, 2026)
The banking transformation is necessary to maintain a competitive edge and resilience in a dynamic, technology-driven environment. Despite the growing body of scholarship on this subject, the transformation of banking resilience remains insufficiently understood, particularly in the context of the technology-driven environment. This study examines the key factors that underpin successful digital transformation in the banking sector and evaluates how such transformation contributes to resilience. To achieve this, a systematic literature review was conducted, examining peer-reviewed academic articles published between 2016 and 2025. The findings highlight that successful digital transformation in banking depends on technology readiness, organizational culture, strong leadership support, and a robust regulatory framework, all of which are essential for driving innovation and resilience. By adopting an integrated analytical approach, this research contributes to understanding how banks can address the challenges of digital transformation and improve their resilience.